Analysis of National Hospital Quality Indicator Achievement among Hospitals in Karawang Regency, Indonesia - Dian Agnesa Sembiring; Iha Nursolihah; Muhammad Irfan (MEDFARM: Jurnal Farmasi dan Kesehatan, 2026)
The National Hospital Quality Indicators (NHQI) are a set of indicators used to assess the quality of hospital services at the national level. However, the implementation of NHQI in Indonesia still shows variations in quality indicator achievements among hospitals, both in terms of reporting compliance and the attainment of specific indicator targets, including in Karawang Regency. This study aimed to analyze the achievement of thirteen NHQI indicators in Karawang Regency. This study employed a cross-sectional design with a descriptive quantitative approach through secondary data analysis. The research sample consisted of 24 hospitals that had reported NHQI achievements in April 2026 and had completed the NHQI reporting comprehensively, which were then analyzed using univariate analysis. In general, the characteristics of hospitals in Karawang Regency were predominantly private hospitals, Class B hospitals, and General Hospitals. Most NHQI indicators showed high levels of achievement, with the highest mean score observed for complaint response time (Mean ± SD: 99.9 ± 0.6). However, compliance with fall risk prevention measures (Mean ± SD: 94.1 ± 16.3) and compliance with physician ward visit schedules (Mean ± SD: 79.8 ± 18.8) remained below their respective national targets. Complaint response time demonstrated the highest level of compliance, with 100.0% of hospitals meeting the established standard, followed by compliance with the National Formulary (91.7%). In contrast, PPE compliance showed the highest proportion of hospitals failing to meet the target (58.3%), while compliance with patient identification and fall risk prevention measures also showed unmet proportions of 41.7% each. Therefore, targeted improvement strategies are needed, particularly for indicators with a high proportion of unmet targets and those with N/A data. From a policy perspective, the Karawang District Health Office and hospital management should strengthen monitoring systems, standardize reporting procedures, and provide regular performance feedback to ensure more complete, accurate, and consistent NHQI reporting across hospitals.